Implementasi Pendidikan Spiritual dan Akhlak di MAN 1 Pekalongan - Achmad Erwin Santoso (Indonesian Journal of Islamic Education Studies (INJURIES), 2024)
Spiritual and moral education has an important role in forming the character of students, especially in the madrasa environment. This research aims to analyze the implementation of spiritual and moral education at MAN 1 Pekalongan, with a focus on approaches, strategies and challenges faced. A qualitative approach was used in this research through observation, in-depth interviews and documentation. The research results show that MAN 1 Pekalongan integrates spiritual and moral values into the formal curriculum and extracurricular activities, such as Islamic studies, congregational prayers, and social activities. The strategies implemented include familiarization and strengthening Islamic culture in the madrasa environment. However, the main challenge faced is the gap in the implementation of these values in the family and community. The implementation of spiritual and moral education has succeeded in having a positive impact on student behavior, but requires further synergy between the Madrasah, family and community for more optimal results. Keywords: Implementation of Education; Spiritual Education; Moral Education